ANALISIS PENGARUH VARIAN PRODUK, KUALITAS PRODUK DAN LOKASI TERHADAP VOLUME PENJUALAN DI BRIGHT TERAS BOYOLALI DI BOYOLALI - Pamungkas, Agus Tri; Rahayu, Listyowati Puji; Ria Safitri, Unna; Kistiani Heggy Suryana, Alean; Sri Anggorowati, Luki (Universitas Boyolali, 2025)
Analyzing the effect analysis of product variants, product quality and location on sales volume at the Bright Store Teras Boyolali is a goal in this study. random sampling technique which is the basis for determining the population. The technique used in data collection is the distribution of questionnaires or questionnaires as many as 100 samples. Quantitative method is the method used in this research. Instrument testing is carried out by using the validity test, the reliability of the classical assumption test, the hypothesis test to determine the relationship between variables. Based on the results of this study, it shows the hypothesis t test or partial test of the product variant variable which shows the result that t count 2,983 > t table 1,660 and a significant value of 0.004 <0.05 so that it is stated that H1 is accepted based on the hypothesis assumptions from the partial test and for the product quality variable it is proven by the hypothesis which states that t count 1,825 > t table 1,660 and a significant value of 0.000 <0.05 means that H2 is accepted based on the hypothesis assumptions from the partial test or t test and the location variable from the results of the partial test hypothesis which states t count 1,223 < t table 1,660 and a significant value of 0.224 > 0.05 this proves that location has no significant effect on sales volume